U-Th dating of carbonate platform and slope sediments - Henderson, G. M.; Slowey, N. C.; Fleisher, M. Q. (Geochimica Et Cosmochimica Acta, 2001)
Absolute chronology of marine sediment beyond the C-14 age range provides a test for models of climate change and has many other applications. U-Th techniques have been used for such chronology by dating corals, but extending these techniques to marine sediment is complicated by the presence of significant initial Th-230-both in detrital material and scavenged from seawater. In this study, we investigate four methods of solving the initial Th-230 problem for a particular type of marine sediment-the aragonite-rich sediments of carbonate platforms and slopes. Bulk sediment U-Th analyses can be corrected for initial Th to yield ages with approximate to2 to 3 kyr precision for highstand periods when sediment aragonite contents are particularly high. Uncertainty on the corrections causes inadequate precision for sediment from other periods, however. Removal of scavenged Th before analysis would enable a dramatic increase in this precision but has not proved successful despite a range of chemical leach approaches. Using heavy liquids to separate the various carbonate minerals found in Bahamas sediment enables an isochron approach to correct for initial Th, but the presence of initial Th from two sources requires correction or removal of one source of initial Th before the other is deconvolved by the isochron. Quantitative removal of detrital material before isochron analysis proves a successful approach. Such isochron data demonstrate that, although sediment remains closed to U-Th on a centimetre scale, nuclides are moved from grain to grain by alpha -recoil. Such intergrain exchange is expected to be observed in all sediments containing mineral grains with different U concentrations. Measured U-234/U-238 allows the recoil movement to be corrected and results in isochron ages with precision sometimes as low as 3 kyr. The accuracy of this approach has been proved by dating samples within the 14C age range. Sediments spanning the penultimate deglaciation have also been dated. After a small correction for bioturbation, the age for this event is found to be 135.2 +/- 3.5 ka. TWs date is approximate to8 kyr before the peak in northern hemisphere insolation and suggests that deglaciation is initiated by a mechanism in the southern hemisphere or tropics. This isochron approach shows considerable promise for dating of sediments older than this event, which will provide further information about the timing and mechanisms of global climate change. Copyright (C) 2001 Elsevier Science Ltd.
462zlTimes Cited:49Cited References Count:44

Evidence from U-Th dating against Northern Hemisphere forcing of the penultimate deglaciation - Henderson, G. M.; Slowey, N. C. (Nature, 2000)
Milankovitch proposed that summer insolation at mid-latitudes in the Northern Hemisphere directly causes the ice-age climate cycles. This would imply that times of ice-sheet collapse should correspond to peaks in Northern Hemisphere June insolation. But the penultimate deglaciation has proved controversial because June insolation peaks 127 kyr ago whereas several records of past climate suggest that change may have occurred up to 15 kyr earlier. There is a clear signature of the penultimate deglaciation in marine oxygen-isotope records. But dating this event, which is significantly before the 14C age range, has not been possible. Here we date the penultimate deglaciation in a record from the Bahamas using a new U-Th isochron technique. After the necessary corrections for alpha-recoil mobility of 234U and 230Th and a small age correction for sediment mixing, the midpoint age for the penultimate deglaciation is determined to be 135 +/- 2.5 kyr ago. This age is consistent with some coral-based sea-level estimates, but it is difficult to reconcile with June Northern Hemisphere insolation as the trigger for the ice-age cycles. Potential alternative driving mechanisms for the ice-age cycles that are consistent with such an early date for the penultimate deglaciation are either the variability of the tropical ocean-atmosphere system or changes in atmospheric CO2 concentration controlled by a process in the Southern Hemisphere.
HendersonSloweyengEngland2000/03/15 09:00Nature. 2000 Mar 2;404(6773):61-6.

Cool surface waters of the subtropical North Pacific Ocean during the last glacial - Lee, K. E.; Slowey, N. C. (Nature, 1999)
One of the most controversial results of the CLIMAP(1,2) project's reconstruction of past sea surface temperature (SST) is that large areas of the subtropical Pacific Ocean were warmer during the last glacial period than they are today. This finding has important implications because SST patterns at low to subtropical latitudes strongly influence climate, and SST changes are closely linked with climate fluctuations(3-5). Until now, a lack of well-preserved, high-resolution marine sediment cores from the region has hindered efforts to confirm these unexpectedly high ice-age SST estimates. Here we use both the oxygen-isotope compositions and species assemblages of planktonic foraminifera in a shallow-water core with high deposition rates near Hawaii to estimate glacial SST of the subtropical North Pacific Ocean, Contrary to the CLIMAP results(2), our data indicate that the annual average SST in this region was similar to 2 degrees C cooler during the last glaciation than it is today, These results help to reconcile the marine SST record with inferences drawn from snowline depressions on Hawaii during the last glacial(3,6), and should ultimately yield improved estimates of global climate sensitivity by providing important new constraints on climate model simulations of ice-age cycles.
166knTimes Cited:31Cited References Count:29

The overturning circulation of the glacial Atlantic: A view from the top - Lynch-Stieglitz, J.; Curry, W. B.; Slowey, N. C. (Sixth International Conference on Paleoceanography, 1999)
id: 1337

Direct U-Th dating of marine sediments from the two most recent interglacial periods - Slowey, N. C.; Henderson, G. M.; Curry, W. B. (Nature, 1996)
A KNOWLEDGE of the age of marine sediments is necessary to determine the timing of events and rates of processes in the marine realm, and the relationships among marine and other climatically sensitive records. The establishment of an accurate chronology for Pleistocene marine sediments beyond the range of radiocarbon dating (approximately the past 45 kyr) has therefore been a goal of palaeoceanographers for decades. Early attempts(1,2) based on measurements of the radionuclides Th-230 and Pa-231 mere beset with problems, and subsequent studies focused on tying fluctuations in marine sediment oxygen-isotope records to events such as the formation of col al reef terraces and changes in the Earth's magnetic polarity(3,4), and tuning the resultant chronologies to the Earth's orbitally driven insolation variations(5-8). But these chronologies (especially the age and duration of the last interglacial period) have been challenged by several studies(9-12), raising questions about the fundamental cause of Pleistocene climate fluctuations. Here we report the direct U-Th dating of aragonite-rich marine sediments from the Bahamas, and present an accurately dated marine oxygen-isotope record for the last two interglacials. We obtain dates of 120-127 kyr BP for the last interglacial and 189-190 kyr np for the late stage 7 interglacial. These dates are in accord with the general theory of orbitally forced climate fluctuations and demonstrate the potential of our direct-dating approach for developing an absolute chronology for the Pleistocene marine oxygen-isotope record.
Vh315Times Cited:39Cited References Count:40

Glacial-Interglacial Differences in Circulation and Carbon Cycling within the Upper Western North-Atlantic - Slowey, N. C.; Curry, W. B. (Paleoceanography, 1995)
We investigated glacial-interglacial changes in the circulation and carbon cycling in the western North Atlantic subtropical gyre using hydrographic data and downcore records of the stable isotopic compositions of individual shells of Bahamian benthic foraminifera. Potential temperature-salinity-depth relations show that modern thermocline (similar to 200-1000 m) and deep (similar to 1000-2000 m) waters in the Providence Channels, Bahamas, originate in the Sargasso Sea and are typical of the subtropical gyre. Gradients in the stable isotopic compositions of late Holocene Planulina and Cibicidoides species from the bank margins (similar to 400 to 1500 m depth) reflect temperature, nutrient, and isotopic gradients of modern subtropical gyre waters. The difference between the delta(18)O of glacial maximum and late Holocene foraminifera is similar to 2.1 parts per thousand for the upper 900 m of the water column and similar to 1.6 parts per thousand for deeper waters, indicating that these waters were similar to 4 degrees C and similar to 2 degrees C cooler, respectively, during glacial time. The glacial temperature gradient (dT/dz) was similar to today, while the base of the thermocline was similar to 100 m shallower. These results differ significantly from our earlier results from multiple shell delta(18)O analyses, which implied upper thermocline waters were only similar to 1 degrees C cooler and dT/dz was greater during the glacial maximum. The difference occurs because bioturbation adversely affects multiple shell analyses of glacial-aged samples from shallow water depths. At all depths above 1500 m, foraminiferal delta(13)C are greater during the glacial maximum than the late Holocene by at least 0.1 to 0.2 parts per thousand (as much as 0.6 parts per thousand in the lower thermocline), indicating that nutrient concentrations throughout the thermocline were reduced and there was no oxygen minimum zone during the glacial maximum. This suggests greater, more uniform ventilation of the thermocline. Results of single and multiple shell delta(13)C analyses of glacial age foraminifera compare favorably because samples most affected by mixing correspond to water depths where the glacial-interglacial change of delta(13)C was small. Cooler upper ocean waters during the glacial maximum reflect cooler temperatures at the ocean surface where isopycnal surfaces outcrop, including large areas of the subtropical ocean. A shallower thermocline base is consistent with southward migration of the northern edge of the subtropical gyre or increased mode water production. Enhanced thermocline ventilation is consistent with more vigorous winds and all isopycnal surfaces outcropping in the area of Ekman downwelling.
Rm032Times Cited:80Cited References Count:86